2009
DOI: 10.1002/bjs.6811
|View full text |Cite
|
Sign up to set email alerts
|

p38 Mitogen-activated protein kinase signalling regulates vascular inflammation and epithelial barrier dysfunction in an experimental model of radiation-induced colitis

Abstract: : p38 MAPK is an important signalling pathway in radiation-induced colitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 42 publications
(56 reference statements)
1
20
0
Order By: Relevance
“…After TBI, Akt/mTOR and their active forms, Notch, beta-catenin, NFkB, and their downstream targets were markedly downregulated in IECs from Villin Cre ;Dclk1 f/f mice compared with IECs from Dclk1 f/f mice. Intestinal epithelial integrity is a necessary component in maintaining intestinal epithelial homeostasis and during regeneration after injury5253. Loss of intestinal epithelial integrity and increased permeability due to impaired expression of tight and adherens junction proteins in Villin Cre ;Dclk1 f/f mice, even 3.5 days post-TBI, may account for defective restitution responses.…”
Section: Discussionmentioning
confidence: 99%
“…After TBI, Akt/mTOR and their active forms, Notch, beta-catenin, NFkB, and their downstream targets were markedly downregulated in IECs from Villin Cre ;Dclk1 f/f mice compared with IECs from Dclk1 f/f mice. Intestinal epithelial integrity is a necessary component in maintaining intestinal epithelial homeostasis and during regeneration after injury5253. Loss of intestinal epithelial integrity and increased permeability due to impaired expression of tight and adherens junction proteins in Villin Cre ;Dclk1 f/f mice, even 3.5 days post-TBI, may account for defective restitution responses.…”
Section: Discussionmentioning
confidence: 99%
“…While little is known about the role of NF-B in determining the contribution of IECs to C. rodentium colitis, we and others recently showed that IEC-specific p38 MAPK signaling plays a major role in the immune and inflammatory response to C. rodentium infection (25,42), in keeping with our findings that the ⌬nleC strain triggered greater chemokine responses in vivo. It has been recently reported that p38 MAPK modulates NF-B signaling during C. rodentium infection (4), and both of these signaling pathways are important in MIP-2, MIP-3␣, and KC production by epithelial cells (33,39,51). By suppressing both NF-B and p38 MAPK activation, C. rodentium likely suppresses the local inflammatory response, creating a protected niche in the intestine.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the chemokine-mediated mechanisms behind accumulation of neutrophils in the lung are relatively well known, whereas the signaling pathways regulating M1 protein-induced neutrophil recruitment and tissue damage in the lung remain elusive. A broad range of stress stimuli, such as ischemia/reperfusion [14,15], radiation [16], heat shock [17], microbial toxins [18], and infections [19,20], is integrated and transmitted intracellularly via MAPKs, including p38 MAPK, ERK1/2, and JNKs [21]. Signal transduction through MAPKs controls production of proinflammatory cytokines and chemokines [22][23][24].…”
Section: Introductionmentioning
confidence: 99%